The Schottky barrier modulation at PtSi/Si interface by strain and structural deformation - Srivastava, Pooja; Shin, Mincheol; Lee, Kwang-Ryeol; Mizuseki, Hiroshi; Kim, Seungchul (AMER INST PHYSICS, 2015)
We show, using density functional theory (DFT) calculations, that the Schottky barrier height (SBH) at the PtSi/Si interface can be lowered by uniaxial strain applied not only on Si but also on PtSi. The strain was applied to the (001) direction of Si and PtSi, which is normal for the interface. The SBH of the hole is lowered by 0.08 eV under 2% of tensile strain on Si and by 0.09 eV under 4 % of compressive strain on PtSi. Because the SBH at PtSi/Si contact is approximately 0.2 eV, this amount of reduction can significantly lower the resistance of the PtSi/Si contact; thus applying uniaxial strain on both PtSi and Si possibly enhances the performance of Schottky barrier field effect transistors. Theoretical models of SB formation and conventional structure model are evaluated. It is found that Pt penetration into Si stabilizes the interface and lowers the SBH by approximately 0.1 eV from the bulk-terminated interface model, which implies that conventionally used bulk-terminated interface models have significant errors. Among the theoretical models of SB formation, the model of strong Fermi level pining adequately explains the electron transfer phenomena and SBH, but it has limited ability to explain SBH changes induced by changes of interface structure. (C) 2015 Author(s). All article content, except where otherwise noted, is licensed under a Creative Commons Attribution 3.0 Unported License.
Keywords: IN-DIFFUSION; TOTAL-ENERGY; SI; SEMICONDUCTOR; HEIGHT; SILICON; MOSFET; MODEL